Recent Progress in Technetium-99m-Labeled Nanoparticles for Molecular Imaging and Cancer Therapy - Sajid Mushtaq (MDPI AG, 2021)
Nanotechnology has played a tremendous role in molecular imaging and cancer therapy. Over the last decade, scientists have worked exceptionally to translate nanomedicine into clinical practice. However, although several nanoparticle-based drugs are now clinically available, there is still a vast difference between preclinical products and clinically approved drugs. An efficient translation of preclinical results to clinical settings requires several critical studies, including a detailed, highly sensitive, pharmacokinetics and biodistribution study, and selective and efficient drug delivery to the target organ or tissue. In this context, technetium-99m (99mTc)-based radiolabeling of nanoparticles allows easy, economical, non-invasive, and whole-body in vivo tracking by the sensitive clinical imaging technique single-photon emission computed tomography (SPECT). Hence, a critical analysis of the radiolabeling strategies of potential drug delivery and therapeutic systems used to monitor results and therapeutic outcomes at the preclinical and clinical levels remains indispensable to provide maximum benefit to the patient. This review discusses up-to-date 99mTc radiolabeling strategies of a variety of important inorganic and organic nanoparticles and their application to preclinical imaging studies.